Effects of soil management and deficit irrigation strategies on physiological and agronomical responses of Aragonez field-grown grapevines - Santos, T.P. (2022)
The use of irrigation in Mediterranean viticulture is now a common practice in intensive grapevine production to improve quality of production. The negative effects of water deficits on grape berry development are well known but the underlying mechanisms remain not fully understood. To avoid the unfavourable impacts of mechanization on the soil structure and biology some farmers are using cover crops on their vineyards. Within this frame we have compared the traditional soil tillage with a high level of mechanization with other system where we maintained a permanent soil cover between the rows. In both soil systems we tested three different irrigation treatments, deficit irrigation (DI - 40% of evapotranspiration (ETc)); regulated deficit irrigation (RDI); partial root drying (PRD) while in the soil cover treatment we also studied the full irrigation (FI) and the non irrigation (NI) treatments. Compared to soil tillage the resident vegetation reduced soil water content during late Spring, before irrigation started, inducing a significant reduction on vine vegetative growth berry weight and yield. Among irrigation strategies only RDI treatment showed a significant reduction in the lateral leaf area development, berry weight and yield when compared to PRD and DI treatments which presented similar values. No significant differences were observed in berry composition either for the two floor management practices or for the three irrigation strategies